2018
DOI: 10.1038/s41598-018-26765-y
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis-infected cells and uninfected-bystander cells exhibit diametrically opposed responses to interferon gamma

Abstract: The intracellular bacterial pathogen, Chlamydia trachomatis, is a tryptophan auxotroph. Therefore, induction of the host tryptophan catabolizing enzyme, indoleamine-2,3-dioxgenase-1 (IDO1), by interferon gamma (IFNγ) is one of the primary protective responses against chlamydial infection. However, despite the presence of a robust IFNγ response, active and replicating C. trachomatis can be detected in cervical secretions of women. We hypothesized that a primary C. trachomatis infection may evade the IFNγ respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 66 publications
(68 reference statements)
0
16
0
1
Order By: Relevance
“…This, in turn, activates the JNK pathway ( 9) resulting in a decrease of E2F1 expression in bystander cells (10). Echoing the effect in infected cells, E2F1 downregulation decreases the expression of numerous miRNAs (11), with a net effect of priming these cells for Salmonella infection, by favoring bacterial binding to bystander cells, as well as by promoting bacterial internalization and intracellular replication (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, activates the JNK pathway ( 9) resulting in a decrease of E2F1 expression in bystander cells (10). Echoing the effect in infected cells, E2F1 downregulation decreases the expression of numerous miRNAs (11), with a net effect of priming these cells for Salmonella infection, by favoring bacterial binding to bystander cells, as well as by promoting bacterial internalization and intracellular replication (12).…”
Section: Methodsmentioning
confidence: 99%
“…In this case, reactive oxygen intermediates mediate the paracrine activation of bystander cells. Similarly, during Chlamydia trachomatis infection the response of infected cells to interferon-γ is blocked, whereas that of bystander cells is unhindered contributing to limiting the spread of infection 12 . Along the same line, we have shown that Shigella flexneri infection induces plasma membrane remodeling in infected and bystander cells, through the activation of the acid sphingomyelinase and strong accumulation of ceramide at the cell surface 13 .…”
mentioning
confidence: 99%
“…A recent example demonstrated the modulation of STAT1 phosphoactivated in response to IFN-γ. Ibana et al (2018) reported that in infected endocervical epithelial cells, phosphorylated STAT1 (pSTAT1) did not translocate to the nucleus, in contrast to observations in neighboring uninfected cells. Transcription mediated by the AP-1- transcription factor was also enhanced in C. trachomatis -infected HeLa cells through the indirect action of C. trachomatis via the host proteins Pin1 and Men1, which are known AP-1 regulators (Olive et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
“…A recent study has identified an additional immune evasion tactic employed by C. trachomatis that blocks the host cell's response to IFN-γ. As a result only (uninfected) bystander cells can respond to IFN-γ, preventing the spread of the infection beyond the initially infected cell (Ibana et al, 2018). Timing appears to be critical as the authors found that pre-treatment of cells with IFN-γ prevents progression of C. trachomatis along the normal developmental cycle, whereas an existing infection will block IDO-1 expression.…”
Section: Discussionmentioning
confidence: 99%